(untitled) (Fiep Bulletin - online, 2014)
A good job opportunity is more and more related to education level. Millions of adolescents try to go to a university through college entrance exam. The preparatory period for these tests was stated that provokes alterations in students’ lifestyle, and also with typical changes during adolescence can generate a stress condition. The objective of this research was to evaluate the lifestyle profile of a group of students from a preparatory test exam course from the Federal University of Santa Catarina. It was founded that the subjects presented a lifestyle profile considered as regular, with positive answers regarding preventive behavior and relationships, however, negative answers for physical activity, framing them as insufficiently active, irregular habits and high stress perception. So, the research concludes that the adolescents studied are in a preoccupying situation, for the fact that they are in a important phase to chose habits for their adult life; and also it was evidenced the need of incentives for the implantation of programs that would help in education for Physical Activity and Health.